2024
DOI: 10.1042/bsr20240249
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance spectroscopy reveals biomarkers of stroke recovery in a mouse model of obesity-associated type 2 diabetes

João P.P. Vieira,
Dimitra Karampatsi,
Ellen Vercalsteren
et al.

Abstract: Obesity and Type 2 diabetes (T2D) are known to exacerbate cerebral injury caused by stroke. Metabolomics can provide signatures of metabolic disease, and now we explored whether the analysis of plasma metabolites carries biomarkers of how obesity and T2D impact post-stroke recovery. Male mice were fed a high-fat diet (HFD) for 10 months leading to development of obesity with T2D or a standard diet (non-diabetic mice). Then, mice were subjected to either transient middle cerebral artery occlusion (tMCAO) or sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Prior research has indicated a significant association between T2D and circulating amino acids ( 18 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has indicated a significant association between T2D and circulating amino acids ( 18 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the majority of these studies did not systematically and comprehensively present the associations. For instance, some studies merely compared amino acid profiles without exploring their correlations with diabetes ( 18 , 19 ), while others had a limited number of participants ( 20 ). Previous studies also identified various amino acids that may be strongly linked to T2D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation